Exochaenium natalense (Gentianaceae), a reinstated taxon endemic to KwaZulu-Natal, South Africa - Kissling, Jonathan; Grieve, Kate W.; Grieve, Graham; Bytebier, Benny (Phytotaxa, 2023)
Based on morphological and ecological considerations, Belmontia natalensis (syn. Exochaenium grande var. homostylum) is reinstated as Exochaenium natalense (Gentianaceae). It only occurs in a section of the coastal region of the Eastern Cape (Pondoland) and southern KwaZulu-Natal provinces, South Africa. Exochaenium natalense differs from E. grande, the only other South African Exochaenium taxon, by having smaller flowers (corolla diameter < 2 cm vs > 3 cm) with a different colour (white vs cream-salmon or yellow). Because the type material of E. natalense consists of two sheets, a lectotype is designated.